Photography as a dine arts medium in post-communist countries. The Case of Romania - Orosan-Telea, Maria (Revelar: Journal of Photography and Image Studies, 2016)
This paper aims to analyze the most important trends in the post-communist Romanian photography, emphasizing those who which are based on a critical dialogue with the inheritance of the dictatorial regime. Recording with a lucid eye the industrial urban landscape or the everyday life of the transitional society, the results of photography practice are an important depository of the collective memory. Even though during the socialist period, photography was not taken into account very much by Romanian artists, after the fall of the dictatorial regime, in early 90's, this medium integrated itself rather quickly in the new artistic discourses, as did other form of art that had been suppressed before. The first visible reaction of the artistic environment after the release from the censorship was to recuperate very fast the trends that succeeded in the Western art in the last 40 years. In order to harmonize with the European educational system, the four Romanian higher education institutions of fine arts established new photo-video departments. A wole new generation of artists with mjor interest in photography was emerging.